Innovation-enhanced rubrics assessment for final year projects - Mohd Sharef, Nurfadhlina; Hamdan, Hazlina; Madzin, Hizmawati (World Institute for Engineering and Technology Education, 2014)
Rubrics provide standard isation in evaluation by specifying guidelines to assign marks according to predetermined evaluation criteria. Rubrics-based evaluation for the final year project in computer science has typically focused on the proposal writing, seminar, prototype development, logbook maintenance and dissertation writing. However, the evaluation has often overlooked the innovativeness of the project and the entrepreneurship skills of the candidates. This article addresses the gap in implementation of the final year project and introduces a framework of innovation-enhanced rubrics-based evaluation for the final year project. The new assessment framework emphasises entrepreneurship and innovation skills, which are realised as cognitive, affective, psychomotor and soft skills, as well as life-long learning characteristics in the course implementation. The new framework has resulted in candidates who have acquired the holistic attributes of excellent fresh graduates which are important and highly regarded by employers.